atmospheric etudes: no 1, troposphere - Conrad, Mari Alice (My University, 2021)
As a fourth-year music composition major at MacEwan University, Mari Alice Conrad was interested in exploring the concept of vulnerability. She was particularly inspired by her recent vulnerable experiences returning to school as a mature student and sought to understand these existential experiences in more depth. This curiosity led Conrad to design a research-creation project in her Ethnomusicology course that utilized her skills in composing a musical work that explored vulnerability on three distinct levels: personal vulnerability, societal vulnerability, and global vulnerability. The first level, personal vulnerability, plunged into Conrad's personal experiences as a mature student who, by age and life experience, had been socially segregated to a minority group, and how she was processing those experiences. The second level, sociological vulnerability, specifically focused on addressing societal traditions of classical music and notational conventions for the piano. Conrad sought to displace the customary approach she had developed with the instrument since childhood and considered ways to make the piano (an inanimate object) and its notated music vulnerable. The third level was a more global, ecological, or environmental vulnerability of the weather systems found in the troposphere, the first layer of the atmosphere. Conrad wanted to understand why this layer was extremely volatile and susceptible to multiple variables and how humans interacted with the vulnerability of this force. This third level was also an area that she could universally connect with her audience (hence the title of the composition) and acted as a bridge to explore the other two levels of vulnerability in her work. Throughout the research-creation process, Conrad was able to explore the three levels of vulnerability in tremendous depth, express her interactions and discoveries of these three levels, and further disseminate her findings through notating a graphic score, recording the composition, and crafting an audiovisual representation. The final result of the research-creation composition project (music score and video) brilliantly weaves together concepts of vulnerability in a compelling and meaningful way and shares insight into how these ideas influence and encapsulate Conrad's budding artistic practice.
Keywords: vulnerability; composition; musical scores